Avaliação do papel da fibrina rica em plaquetas em defeito crítico cirurgicamente criado em calota de ratos induzidos à hipercolesterolemia tratados ou não com atorvastatina - Oliva, André Hergesel de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Esse estudo objetivou-se em avaliar o papel da membrana de fibrina rica em plaquetas na reparação óssea em defeito crítico de calota de ratos induzidos à hipercolesterolemia, bem como a atuação do tratamento de atorvastatina nesse processo. Quarenta defeitos críticos de 6 mm de diâmetro foram criados em calotas cranianas de ratos. Cada defeito foi aleatoriamente dividido em 8 grupos experimentais (GC, GCPRF, GCA, GCH, GHA, GPRFA, GPRFH, GPRFHA), avaliados aos 28 dias pós-operatórios com análises histológica e microtomográfica. Os resultados mostraram que houve formação óssea em todos os grupos analisados. O grupo GPRFH apresentou formação óssea mais acentuada com relação aos demais grupos. Dos grupos em que foi administrado atorvastatina, o GPRFHA apresentou maior taxa de formação óssea (p < 0,05). Com a metodologia utilizada, a fibrina rica em plaquetas, quando associada à condição de hipercolesterolemia, induziu ao aumento da formação óssea.

Objectives: The aim of this study was to evaluate the efficacy of Platelet Rich Fibrin (PRF) in the healing process of surgically created critical-size defects in rat calvarial induced to hypercholesterolemia treated or not with atorvastatin. Materials and method: 40 critical defects were created with 6 mm diameter calvaria of rats. Each defect was randomly divided into eight experimental groups (GC, GCPRF, GCA, GCH, GHA, GPRFA, GPRFH, GPRFHA), evaluated at 28 postoperative days for histomorphometry and microtomography. Results: The results showed new bone formation in all groups. The GPRFH group just did differ from all groups in the new bone formation (p < 0.05). Among the groups treated with atorvastatin, the GPRFHA group showed the highest bone formation rate. Conclusion: With the methodology used, the platelet-rich fibrin associated with the hypercholesterolemia induced to new bone formation. Clinical relevance: Based on these results, it is necessary to unveil the mechanisms of the association of platelet-rich fibrin with hypercholesterolemia and how it interferes in PRF microstructure and bone regeneration, to confer clinical predictability in patients in this condition who will undergo bone reconstruction and implant rehabilitation.
Evaluation of the role of Platelet Rich Fibrin in surgical critical-size calvarial defect in rats with diet-induced hypercholesterolemia treated or not with atorvastatin
Keywords: Hypercholesterolemia; Atorvastatin calcium; Hipercolesterolemia; Atorvastatina cálcica; Plaquetas; Regeneração óssea; Boné regeneration; Platelets